Proses Sosiokultural Siswa Dalam Pendidikan Multikultural di Sekolah Dasar - Rifky Setiawan (Universitas Negeri Makassar, 2023)
The purpose of this research is to look at students' sociocultural processes in multicultural education in elementary schools. This research is a type of qualitative research with a phenomenological approach, namely by conducting a critical analysis of social events. Data collection techniques are carried out by observation, interviews, and documentation. The results of the study show that at SD SD Negeri 008 Sidodadi the teachers have integrated students' socio-culture into multicultural education through a learning model at school. This is seen as important to provide provision and help develop insight into thinking and personality and to train students in dealing with social problems that occur in their community environment.